2016
DOI: 10.1159/000452893
|View full text |Cite
|
Sign up to set email alerts
|

Impact of <b><i>Pseudomonas aeruginosa</i></b> Infection on Respiratory Muscle Function in Adult Cystic Fibrosis Patients

Abstract: Background:Pseudomonas aeruginosa infection impairs respiratory muscle function in adolescents with cystic fibrosis, but its impact on adult patients has not been characterised. Objectives: To investigate respiratory muscle function in adult cystic fibrosis patients according to P. aeruginosa status (repetitive samples over 12 months). Methods: The pressure-time index of the respiratory muscles (PTImus), a measure of their efficiency, served as the primary outcome. In addition, respiratory load and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
1
3
0
2
Order By: Relevance
“…The study used similar methodology and contrasted the results of a previous study of ours in adolescents with CF, where we found that chronic Pa infection was an independent determinant of PTI mus [2]. Magnet et al [1], thus, suggested that the findings in adolescent CF patients cannot be extrapolated to the adult CF population.…”
Section: Funding Sourcessupporting
confidence: 65%
See 2 more Smart Citations
“…The study used similar methodology and contrasted the results of a previous study of ours in adolescents with CF, where we found that chronic Pa infection was an independent determinant of PTI mus [2]. Magnet et al [1], thus, suggested that the findings in adolescent CF patients cannot be extrapolated to the adult CF population.…”
Section: Funding Sourcessupporting
confidence: 65%
“…We read with interest the study by Magnet et al [1] which evaluated the impact of Pseudomonas aeruginosa (Pa) infection on respiratory muscle function in adult cystic fibrosis (CF) patients. The authors studied 51 adults with CF and used the pressure-time index of the respiratory muscles (PTI mus ) to evaluate respiratory muscle efficiency.…”
Section: Funding Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the mentioned respiratory tract infections, there are bacterial infections that affect more females than males. These gender differences have been clearly demonstrated in cystic fibrosis disease (CF) that is characterized by a dysregulated inflammatory response and an altered cytokine profile in the lungs that is associated with a higher prevalence of bacterial infections (mainly due to P. aeruginosa ) and poorer lung and respiratory muscle function in females than in males [ 142 144 ]. Differential estradiol levels between females and males have been proposed as a factor that explains the sexual dimorphism in CF-associated infections because differences in gender lung function are observed after puberty and are correlated with estrogen levels during the menstrual cycle [ 145 ].…”
Section: Bacterial Infections In the Respiratory Tractmentioning
confidence: 99%
“…Entretanto a literatura aponta resultados divergentes sobre os efeitos que as infecções por patógenos podem apresentar na FMR. Enquanto alguns estudos mostram que a presença de infecção por Pseudomonas aeruginosa propicia um aumento da carga do trabalho respiratório, exercendo, assim, um efeito de condicionamento da FMR 6,23,24 . Outras pesquisas 25,26 sugerem que as características da doença crônica, como a desnutrição, infecção recorrente e a hiperinsuflação pulmonar, acabam limitando e diminuindo a FMR.…”
Section: Resultsunclassified